ASSESS THE IMPACT OF DIABETIC NEPHROPATHY ON RENAL HEMODYNAMICS - Sapayeva Z.A; Madaminov X.A (Scholar Express Journals, 2023)
40 patients with type 2 diabetes mellitus (DM) without kidney damage (20 people) and with various stages of diabetic nephropathy caused by DM 2 (20 people) aged 37 to 54 years were examined, and the control group consisted of 20 healthy individuals. The duration of the disease ranged from 6 months to 20 years. We studied such indicators as the results of general blood and urine tests, lipid spectrum, glycemic profile, glycosylated hemoglobin, microalbuminuria, glomerular filtration rate (GFR) according to the CKD-EPI formula, and parameters of intrarenal hemodynamics - Doppler parameters PI, RI, Vmax. An analysis of the data obtained during the study suggests that in DM 2, the kidneys are actively involved in the pathological process already in the very debut of the disease. The appearance of MAU or normally elevated blood pressure in a patient with DM 2 indicates an already advanced pathological process in the kidneys in terms of the possibility of its reverse development
Keywords: Diabetes mellitus; diabetic nephropathy; microalbuminuria